2004
DOI: 10.1073/pnas.0308484101
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of p160ROCK bypasses cell cycle arrest after Aurora-A/STK15 depletion

Abstract: Alterations in the expression and activity of the centrosomal kinase, Aurora-A͞serine͞threonine kinase 15 (STK15), affect genomic stability, disrupt the fidelity of centrosome duplication, and induce cellular transformation. Here, we provide evidence that p160ROCK, a Rho-associate serine͞threonine kinase, associates with Aurora-A in a protein complex with other STK15-associated factors. Suppression of Aurora-A by small interfering RNA in HeLa cells blocks the ability of centrosomes to organize normal mitotic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 46 publications
3
62
0
Order By: Relevance
“…The protein serine/threonine kinases Rho-kinases (or ROCK) are downstream effectors of Rho able to selectively interact with the GTP-bound form of Rho. Moreover, it has recently been demonstrated that p160ROCK is a centrosome component, which functions in centrosome positioning 31 and also with Aurora A controls progression through G2/M, 42 which suggest that this protein may mediate the radioprotective effect of RhoB-F. We have shown that treatment of RhoB-F-expressing cells with the ROCK inhibitor, Y27632, activated mitotic cell death mechanisms and centrosome overduplication after irradiation. The same treatment though has no effect on RhoB-GG cells.…”
Section: Discussionmentioning
confidence: 78%
“…The protein serine/threonine kinases Rho-kinases (or ROCK) are downstream effectors of Rho able to selectively interact with the GTP-bound form of Rho. Moreover, it has recently been demonstrated that p160ROCK is a centrosome component, which functions in centrosome positioning 31 and also with Aurora A controls progression through G2/M, 42 which suggest that this protein may mediate the radioprotective effect of RhoB-F. We have shown that treatment of RhoB-F-expressing cells with the ROCK inhibitor, Y27632, activated mitotic cell death mechanisms and centrosome overduplication after irradiation. The same treatment though has no effect on RhoB-GG cells.…”
Section: Discussionmentioning
confidence: 78%
“…Overexpression or constitutive activation of Aurora-A, results after one or two division cycles in supernumerary centrosomes and multipolar mitotic spindles, dependent on an initial failure of cytokinesis: this is thought to be an important predetermining factor for genomic instability in many cancers (Marumoto et al, 2005). Although the mechanism by which Aurora-A amplification promotes cytokinetic failure remains to be determined, interestingly, Aurora-A and the RhoA effector p160ROCK have been shown to form a complex in mitotic cells, and siRNA depletion of p160ROCK blocked some Aurora-A-dependent defects (Du and Hannon, 2004). Hence, the association of HEF1 with Aurora-A provides a separate means by which Aurora-A might influence RhoA.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, ROCK1 physically associates with STK15, which is implicated in the regulation of the centrosome replication cycle. Suppression of ROCK1 expression by siRNA bypasses G(2)/M cell cycle arrest after STK15 depletion and alleviates apoptosis in HeLa cells [25].…”
Section: In Vitro Evidencementioning
confidence: 99%
“…The small GTP-binding protein RhoE interacts with the N-terminal region of ROCK1 (amino acids 1-420) and prevents Rho binding to RBD [101,112]. Other negative regulators have been found to bind to and inhibit ROCK activity, such as the small GTP-binding proteins, Gem and Rad [145], Raf-1 [107], p21(Cip1/WAF1) [81] and Aurora-A/serine/threonine kinase 15 (STK15) [25]. However, their mechanisms of action are not defined.…”
Section: Regulation Of Rock Activitymentioning
confidence: 99%